Price liberalization in Russia: behaviour of prices, household incomes, and consumption during the first year - Koen, Vincent (IMF WashingtonUS, 1993)
Analyses the behaviour of prices in Russia before and after the January 1992 price liberalization as well as the evolution of wages and overall consumer incomes and expenditure. Emphasises developments in 1992 and compares recent experiences in Central and Eastern Europe. Considers shortages, savings and income distribution.